Optimal operation of microgrid with multi-energy complementary based on moth flame optimization algorithm. Issue 7 (2nd April 2020) - Wang, Yongli; Li, Fang; Yu, Haiyang; Wang, Yudong; Qi, Chengyuan; Yang, Jiale; Song, Fuhao
ABSTRACT: Recently, hybrid distributed generation system has become a popular energy supply mode. It is obvious that the integrated system could improve energy efficiency and reduce costs. However, the system scheduling is a problem that would determine the operation cost. In this paper, a hybrid energy system including wind power, photovoltaics, gas turbines, and energy storage was introduced. In order to obtain the minimum operation cost, an operation optimization model was built. The schedule plan of each unit was optimized by moth flame optimization algorithm. Finally, through empirical research on a microgrid project, the optimization results in three configuration case of wind power, photovoltaics, and storage indicated that the operation optimization model in this paper could effectively reduce system operation cost, and the optimal output plan of each unit was obtained. And it is proved that the model proposed in this paper has a certain guiding role on economically dispatch of hybrid energy system.